2023
DOI: 10.3390/plants12020289
|View full text |Cite
|
Sign up to set email alerts
|

IBA Delivery Technique and Media Salts Affected In Vitro Rooting and Acclimatization of Eight Prunus Genotypes

Abstract: Difficult-to-root plants often perform poorly during acclimatization and in vitro rooting can increase the survival and quality of plants. The influence of auxin application and mineral nutrition on in vitro rooting and subsequent effects on plant quality in eight Prunus genotypes were investigated. Microshoots were rooted in vitro on Murashige and Skoog (MS), ½ MS, Driver and Kuniyuki (DKW), or New Prunus Medium (NPM) media formulations in combination with 15 µM indole-3-butyric acid (IBA), 4-day 15 µM IBA pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This result is consistent with those reported by other researchers regarding the essential role of auxins in plant propagation by cuttings [52][53][54][55][56]. IBA was found to be the most effective in vitro rooting regulator of all three auxins studied, in agreement with results from other studies (57)(58). The results revealed that as the amount of auxin in the culture medium increased, the formation of calluses at the base of micro-shoots occurred.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with those reported by other researchers regarding the essential role of auxins in plant propagation by cuttings [52][53][54][55][56]. IBA was found to be the most effective in vitro rooting regulator of all three auxins studied, in agreement with results from other studies (57)(58). The results revealed that as the amount of auxin in the culture medium increased, the formation of calluses at the base of micro-shoots occurred.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in arabidopsis, IBA promotes adventitious root formation through its conversion to IAA (Veloccia et al, 2016). In successful micropropagation, better shoots with extensive root systems can produce healthy plants under greenhouse conditions (Lawson et al, 2023). In stevia application of 1 mg/l, IBA resulted in the best growth parameters of in vitro formed roots and shoots.…”
Section: Discussionmentioning
confidence: 99%
“…The greenhouse had an average temperature of 25.4 • C ± 3.1 • C (mean ± standard error) and a relative humidity between 42% and 82% receiving natural light and supplemental light for a day length between 6 AM and 10 PM. A total of 24 'Guardian ® ' peach rootstocks (Prunus persica (L.) Batsch, 'Guardian') were propagated using tissue culture one year prior to the study [19]. After a single year of growth, the propagated trees were small and ranged in size from 5 cm to 10 cm tall before being initially potted in 6.8 cm × 22.8 cm × 6.8 cm tree pots (Anderson Pots, Portland, OR, USA) with 50% Fafard 3B potting mix containing Canadian sphagnum peat moss, bark, perlite, vermiculite, dolomitic limestone (Sun Gro Horticulture, Agawam, MA, USA), and 50% sand for approximately 2 months to allow for root development.…”
Section: Design and Treatmentsmentioning
confidence: 99%